Age Estimation in the Living - Ethical and Legal Challenges - Silvina Maria Marques Moura; Áurea Madureira-Carvalho; Álvaro Ferreira de Azevedo; Inês Morais Caldas (RevSALUS, 2025)
INTRODUCTION: The global socioeconomic context, and the migratory flows involved, have led to a pressing demand for age determination in livings. The methodology used to predict age depends on the country's legislation and customs. OBJECTIVES: Identify suggested strategies for dealing with emerging ethical and legal issues related to age estimation in the living. METHODS: A literature search was carried out on contemporary ethical and legal requirements and emerging solutions related to the livings age assessment using the PubMed, Web of Science, and Scopus databases. Exclusion criteria included articles written in languages other than English, studies on non-human subjects, and studies involving cadavers. RESULTS AND DISCUSSION: Chronological age estimation is crucial for human identification, having particular relevance in civil and criminal proceedings [1]. To be ethically acceptable, forensic cases must be decided on the basis of the minimum age principle [2]. The norms of justice, beneficence, no malevolence, and autonomy must be respected [3]. Exposure to ionizing radiation should be as minimal as possible to obtain quality images, in accordance with the ALARA principle [1]. Deep learning platforms are improving the accuracy of age determination by combining information of regions of interest [4]. There is also a growing trend towards the use of non-ionizing techniques, such as ultrasound and magnetic resonance imaging [4,5]. CONCLUSIONS: Ethics and legality must be ensured for age assessment, and certain age groups can be critical in these matters. Technological progress is continually improving the imaging methods. Non-ionizing techniques are environmentally friendly and enable prospective studies.